An introduction to language - Fromkin, Victoria; Rodman, Robert; Hyams, Nina M., 1952- (Australia : Wadsworth, Cengage Learning, 2011)
A classic, known for its comprehensive and balanced coverage, this student textbook now includes contributions from Nina Hyams. The ninth edition reflects new thinking as a result of progress in research in the study of neurolingistics
Previous ed: 2007
Includes bibliographical references and index
Keywords: Language and languages; Linguistics